Desenvolvimento de um modelo matemático e computacional de um forno de recozimento - Carvalho, Solidônio Rodrigues de (2003)
This study presents the development of a mathematical and computational model í°r ,Qn and controlling of an annealing process of silicium Steel strip that occurs in d ing d w industrial furnace. Both the combustion process and the strip heating are simulate □ n* erfo energy and mass balances inside the industrial furnace. These balances are H g3$ considering important variables such as composition, temperature and pressbfe r nC®®' components, adiabatlc flame and environmental temperature. Besides the ba^ optimization technique is implemented in order to estimate the temperature distribUtlO^iz(35 strip at any time. The optimization technique used is the golden section algorithm a least square error function based on difference of the experimental and temperature in two different locations of the strip. All steps of the software devel^^e presented hera: the combustion and annealing process, the energy and mass bala1106 s„jíe<> fundamentais of the optimization process. The efficiency of the software is then den’»1’ ü(,us through an analysis and application of data acquired from operational conditions in annealing lines of a Steel Company. This study is concluded showing a discussio" & uncertainty and error sources the can be present in the resuits The software S>MC°' seems to be a very powedui tool in the simuiation of metal annealing processes.